2021
DOI: 10.3389/fcell.2021.765265
|View full text |Cite
|
Sign up to set email alerts
|

Decidualization Potency and Epigenetic Changes in Human Endometrial Origin Stem Cells During Propagation

Abstract: Human endometrium derived mesenchymal stem cells (hEndSCs) offer a great promise for regenerative medicine and reproductive system disorders treatment methods based on cell therapy due to their broad differentiation potential and highly efficient proliferation. In our study, we investigated the characteristics of hEndSCs that were isolated from two sources: endometrium and menstrual blood, which both contain endometrial origin stem cells. Changes in gene and protein expression levels during long-term cultivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Human decidual stromal cells (hESCs) were induced to decidualize (decidualized hESC: dhESC) according to the above methods [ 14 ]. Western blots revealed that prolactin (PRL) and insulin-like growth factor binding protein 1 (IGFBP1), the traditional markers of decidualization, increased ( Figure 1 E), indicating that in vitro hESC decidualization was successful; moreover, CDH1 increased, and vimentin decreased during hESC decidualization in vitro ( Figure 1 E,G).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human decidual stromal cells (hESCs) were induced to decidualize (decidualized hESC: dhESC) according to the above methods [ 14 ]. Western blots revealed that prolactin (PRL) and insulin-like growth factor binding protein 1 (IGFBP1), the traditional markers of decidualization, increased ( Figure 1 E), indicating that in vitro hESC decidualization was successful; moreover, CDH1 increased, and vimentin decreased during hESC decidualization in vitro ( Figure 1 E,G).…”
Section: Resultsmentioning
confidence: 99%
“…hESCs were cultured in a 5% humidified carbon dioxide atmosphere at 37 °C in phenol red-free Dulbecco’s modified Eagle’s medium (DMEM)/F-12 (Meilunbio, Dalian, China) with 10% foetal bovine serum, 50 mg/mL streptomycin, and 50 U/mL penicillin. One micromolar medroxyprogesterone-17-acetate (MPA) (HY-B0469, MedChemExpress, NJ, USA) and 0.5 mM N6,20-O-dibutyryladenosine cAMP sodium salt (db-cAMP) (HY-B0764, MedChemExpress, Monmouth Junction, NJ, USA) were added to the culture for 6 days to induce hESC decidualization in vitro [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…These ndings could be explained by the activity of hEnSCs. They are characterized by the broad differentiation potential, highly e cient self-renewal and remarkable immunomodulatory capacity to migrate to the injured reproductive tissues caused by chemokines, before they differentiate and integrate somatic cells with non-tumorigenic properties [22,57,58]. It creates conditions for slowing down the progression of brosis and (or) replacing damaged tissues [58-60].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of stem cell surface markers of hDMSCs was characterized by means of flow cytometry. The fluorescence-labeled antibodies were CD90-FITC (Sino Biological, China), CD29-FITC (Sino Biological, China) and CD45-FITC (Sino Biological, China) as previously described [31][32][33].…”
Section: Isolation and Characterization Of Human Dental Mesenchymal S...mentioning
confidence: 99%